2005
DOI: 10.1542/peds.2004-2373
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 2 Influenza Vaccine Schedules in 6- to 23-Month-Old Children

Abstract: When the spring and fall influenza vaccines had the same 3 antigenic components, the early vaccine schedule resulted in similar immunogenicity and reactogenicity compared with the standard schedule. When the vaccine components do not change between years, initiating influenza vaccine in the spring at the time of routine office visits would facilitate full immunization of children against influenza earlier in the season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 22 publications
4
53
1
6
Order By: Relevance
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
“…Classification of fever varied across studies, but a majority of studies [22,25,27,[29][30][31]34,35,37,38] provided data on fever ≥ 38 °C. We used these studies for meta-analysis of fever rate and one additional study [39], where we assumed a fever definition of ≥ 38 °C based on two similar studies by the same lead author [31,35].…”
Section: Characteristics Of Randomised Controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations